1994
DOI: 10.1093/clinids/19.4.746
|View full text |Cite
|
Sign up to set email alerts
|

Pyogenic and Tuberculous Spondylodiskitis (Vertebral Osteomyelitis) in 80 Adult Patients

Abstract: Bacterial spondylodiskitis--i.e., adjacent vertebral osteomyelitis and diskitis--was studied in 80 adult patients. The infection was due to Mycobacterium tuberculosis in 31 cases (39%) and to pyogenic bacteria in 49 cases (61%). The latter pathogens included gram-negative bacilli in 16 cases (20%), Staphylococcus species in 15 (19%), Streptococcus species in 9 (11%), and Corynebacterium species in 1 (1%); the pathogens in the 8 remaining cases (10%) were not identified. Of the patients with tuberculous spondyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
110
4
30

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 234 publications
(156 citation statements)
references
References 14 publications
12
110
4
30
Order By: Relevance
“…Another potential factor to consider in this series is the number of patients with a history of vertebral surgery. Consistent with current data, this is classically associated with a high prevalence of CoNS pathogens (1,2,23,29). Molecular typing allowed us to refine these observations by pinpointing the wide spectrum of staphylococcal species associated with discitis.…”
Section: Diagnosing Infectious Discitis By Dna Analysissupporting
confidence: 81%
See 2 more Smart Citations
“…Another potential factor to consider in this series is the number of patients with a history of vertebral surgery. Consistent with current data, this is classically associated with a high prevalence of CoNS pathogens (1,2,23,29). Molecular typing allowed us to refine these observations by pinpointing the wide spectrum of staphylococcal species associated with discitis.…”
Section: Diagnosing Infectious Discitis By Dna Analysissupporting
confidence: 81%
“…Further identification of infecting bacteria then relies on sequence analysis of amplicons. We decided to design a gram-positive/ gram-negative-specific (rather than a broad) 16S rDNA assay for 3 reasons: 1) the gram-specific amplification strategy appears to be more sensitive than a previous universal 16S rDNA PCR designed in our laboratory (data not shown); 2) exact Gram stain classification by PCR may guide therapeutic decisions; and 3) considering the reported high prevalence of staphylococci in discitis (1,2,23,29), a combination of gram-positive and femA staphylococcal species-specific target genes, as well as a staphylococcal methicillin resistance mecA gene in femA-positive samples, yields a high degree of complementarity. Some samples generated femA amplicons, but no (patient 1) or only very weak (patients 2 and 11) 16S rDNA amplicons, because of the higher sensitivity of a nested femA amplification.…”
Section: Diagnosing Infectious Discitis By Dna Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Other reports have found that generally, spinal infections are more commonly localised to the lower thoracic and lumbar spine. 6,9 Buchelt found no statistical di erence in the level of involvement between those with tuberculous and pyogenic spondylitis.…”
Section: Discussionmentioning
confidence: 93%
“…This was also comparable with the rates (10 ± 42%) reported in other series. 6,9 Recent studies have attributed a rising incidence of spinal infection to increasing intravenous drug abuse. 2,3,5,7,10,12 Interestingly, none of our patients belonged to this high risk group.…”
Section: Discussionmentioning
confidence: 99%